Answer: The Answer Is NOT Letter A
C. y = (x – 2)^2 = Rewrite in vertex form and use this form to find the vertex (
h
,
k
)
. (
2
,
0
) =Already in vertex form. y
=
(
x
−
2
)
^2
Step-by-step explanation: I used math.way
A. y = (x – 2)^2 + 4 = Rewrite in vertex form and use this form to find the vertex (
h
,
k
)
.
(
2
,
4
) =Already in vertex form. y
=
(
x
−
2
)
^2
+
4
B. y = x^2 – 4 = Rewrite in vertex form and use this form to find the vertex (
h
,
k
)
. (
0
,
−
4
) =Find the vertex form. y
=
(
x
+
0
)
^2
−
4
C. y = (x – 2)^2 = Rewrite in vertex form and use this form to find the vertex (
h
,
k
)
. (
2
,
0
) =Already in vertex form. y
=
(
x
−
2
)
^2
D. y = (x – 4)^2 – 4 = Rewrite in vertex form and use this form to find the vertex (
h
,
k
)
. (
4
,
−
4
) =Already in vertex form. y
=
(
x
−
4
)
2
−
4